Report of the Working Group of the Planning Commission on Modernisation of Library Services And Informatics For the Seventh Five Year Plan 1985-90 - Planning Commission (Planning Commission, 1984)
Summary of the report of the working group and financial estimates The planning commission constituted this working group especially to See that library and information services as well as new information technology Are well represented in the 7th plan.
Planning Commission
Planning Commission